PENGARUH TEMPERATUR PADA PEMBENTUKAN BAJA KARBON RENDAH ASTM A36 UNTUK APLIKASI HANGER ROD - Oktadinata, Herry (Jurnal Ilmiah Teknik Mesin, 2016)
In this study tested the tenacity ASTM A36 carbon steel at high temperatures forming in the hanger rod as raw material, in order to obtain the relationship between the temperature of the formability. Research methods include chemical analysis and tensile testing room temperature and high temperature. Then do the formation ofhanger rod of carbon steel ASTM A36 diameter of 16, 20, 24 mm at a temperature of 600, 700, and 800 0C. Then test the hardness and microstructure observation. Tensile test results showed that the tensile strength and yield drops as temperature increases. Microstructure observation indicates the grain size at a temperature of 600 and 700 0C relatively the same, but at a temperature of 800 0C is much greater. Microstructure observation also shows that there are inclusions. Optimal results show that the formation of 600 and 700 0C better than at a temperature of 800 0C. While ductility at 700 0C is better than 600 0C. So the formation of rod hanger at 700 0C is recommended.